Intestinal transcriptome analysis highlights key differentially expressed genes involved in nutrient metabolism and digestion in yellowtail kingfish (Seriola lalandi) fed terrestrial animal and plant proteins - CTM Dam; T Ventura; M Booth; I Pirozzi; Michael Salini; R Smullen; A Elizur (2020)
This study investigated the effects of dietary terrestrial animal and plant proteins on the intestinal transcriptomes of yellowtail kingfish (YTK), Seriola lalandi, an ecologically and economically important marine species in Australia. Five diets containing fish meal (FM), poultry by-product meal (PBM), blood meal (BLM), faba bean meal (FBM) and corn gluten meal (CGM) were formulated and fed over a period of 4 weeks. The Illumina RNA-sequencing (RNA-Seq) results identified a suite of differentially expressed genes involved in nutrient metabolism and protein digestion pathways, reinforced by quantitative polymerase chain reaction (qPCR) results. These findings provide molecular support to the notion that PBM and FBM are useful raw materials in commercial diets for YTK. Using the same evidence, we have demonstrated that BLM and CGM may be less useful and their incorporation into commercial aquafeeds for this species should be done cautiously. The differentially expressed genes showed a subtle difference and high correlation with apparent nutrient digestibility of raw materials. Further, our results indicate that transcriptome profiling provides a useful tool to evaluate alternative protein sources for use in aquaculture feeds.